Religiosidade juvenil em movimento: um estudo de caso Batista Regular - Silva, Valberth Veras da (2009)
The modernity since beginning it was a process of liquefaction and melting of solids (BAUMAN, 2001). By melting of solids he talks about the dissolution of old social order, repudiation and fallen of past, where the tradition reveals solid. There is a crushing of believing and loyalties to this tradition and social order. The post-modernity, comprehended as this melting of solids, brought new ways of live youth and religion. The aim of this research is comprehend the youth religiosity in post-modernity times inside regular Baptist church context. The post-modernity youth religious ethos introduces characteristics of a self-love culture, breaking ideal of live to each other, social relationships fluid, in believing and religious belonging, as well bricolage of believings. This produces a institutional crises and religious transmission inside the Maanaim church. During the research a typology was developed to comprehend the religious movement inside the Maanaim Baptist church. Three types are making: believe with no belonging, given to Satan and orthodox youth. The first type refers to young, going out or staying in church, search a fluid commitment. The second type, talk about the young that broke with dogmas of church and so that are stigmatized. The third type include young that defends the doctrine and practices of church.